Relationship between Trauma-Related Psychotic Reactions and Post-Traumatic Stress Symptoms: The Mediating Role of Alcohol Use - Zhongfang Fu; Wei Xu (International Journal of Psychotherapy Practice and Research, 2017)
This study examined the mediating role of alcohol use in the relationship between PTSD symptoms and trauma-related psychotic reactions. A total of 231 participants including 181 females were recruited via web advertisement and flyers. Alcohol use condition, trauma-related psychotic experience, and PTSD symptoms were measured by Feeling the need to Cut down, Annoyed by criticism, Guilty about drinking, and need for an Eye-opener in the morning (CAGE), Psychosis Screening Questionnaire (PSU) and Short screening scale for posttraumatic stress disorder (SSSP). All the participants were asked to finish the questionnaire package on the Internet and were interviewed later to validate the screening. Logistic regression was used to estimate the mediating effect of alcohol use. Results showed that alcohol use played a mediating role between PTSD symptoms and auditory hallucination while this effect didn’t exist between PTSD symptoms and paranoia. Findings indicated that hallucination and paranoia in people with PTSD symptoms were influenced by alcohol use in diverse ways.
Keywords: PTSD symptoms